Positivization of the Council of Indonesian Ulema’s Halal Fatwa: Policy and Position in Indonesian Legislation - Fuad Mustafid; Khoiruddin Nasution; Ali Sodiqin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Numerous studies have highlighted the significant role of the Council of Indonesian Ulema (MUI) in influencing the development of Islamic law in Indonesia. This has been achieved by integrating several of its legal fatwas into national legislation. However, few studies specifically address the positive impact of MUI's halal fatwas. Additionally, existing research has not thoroughly examined the strategies employed by this fatwa-issuing institution to promote its fatwas, particularly during the reform era. This article explores MUI's essential role and strategic policies during the Reform era in transforming its halal fatwas into state law, as well as the institution's position within Indonesian legislation. The data for this study are derived from official MUI publications, including the Basic Guidelines and Household Guidelines, the outcomes of National Conferences, the results of the Ijtima Ulama Fatwa Commission, the collection of MUI fatwas, and other sources. These data were collected from the Council of Indonesian Ulema's office, libraries, and other information providers. The collected data are then presented and analyzed using the theory of the positivization of Islamic law. This study demonstrates MUI's success and significance in converting its legal fatwas on halal products into state law. Furthermore, this article highlights MUI's crucial role in various regulatory legislations governing halal product assurance. The concept of fatwa positivization, as defined by Qodri Azizy, refers to the process by which MUI effectively integrates its legal fatwas into state law. MUI's approach could serve as one of the potential models or patterns for incorporating Islamic law into national legislation in Indonesia, amidst the ongoing debate on the adoption of Islamic law.